2015
DOI: 10.1007/s13105-015-0392-1
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol improves high-fat diet induced insulin resistance by rebalancing subsarcolemmal mitochondrial oxidation and antioxidantion

Abstract: Although resveratrol (RES) is thought to be a key regulator of insulin sensitivity in rodents, the exact mechanism underlying this effect remains unclear. Therefore, we sought to investigate how RES affects skeletal muscle oxidative and antioxidant levels of subsarcolemmal (SS) and intermyofibrillar (IMF) mitochondrial populations in high-fat diet (HFD)-induced insulin resistance (IR) rats. Systemic and skeletal muscle insulin sensitivity together with expressions of several genes related to mitochondrial biog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 29 publications
(51 reference statements)
1
21
0
Order By: Relevance
“…In mice, resveratrol caused an activation of SIRT1, and its target PGC1-␣, which leads to changes in mitochondrial number and function (Lagouge et al, 2006). Resveratrol intervention also resulted in increased levels of SIRT1, PGC-1␣, and mtDNA copy number, and there was an improvement in high-fat diet-induced insulin resistance (Haohao et al, 2015). Recently it was reported that resveratrol can act as an anti-diabetic agent, due to the repression of the FOXO1 (an important player in insulin signaling) by activation of SIRT1 deacetylase (Sin et al, 2015).…”
Section: Resveratrolmentioning
confidence: 99%
“…In mice, resveratrol caused an activation of SIRT1, and its target PGC1-␣, which leads to changes in mitochondrial number and function (Lagouge et al, 2006). Resveratrol intervention also resulted in increased levels of SIRT1, PGC-1␣, and mtDNA copy number, and there was an improvement in high-fat diet-induced insulin resistance (Haohao et al, 2015). Recently it was reported that resveratrol can act as an anti-diabetic agent, due to the repression of the FOXO1 (an important player in insulin signaling) by activation of SIRT1 deacetylase (Sin et al, 2015).…”
Section: Resveratrolmentioning
confidence: 99%
“…Previous studies have demonstrated that RSV has diverse beneficial health effects including anti-oxidative (17), anti-inflammatory (18), anti-cancer (19), cardioprotective (20) and neuroprotective (21) activities. In relation to diabetic nephropathy, previous reports have indicated that RSV can ameliorate renal insufficiency and pathological changes, as well as prevent high glucose-induced mesangial cell proliferation and glomerular fibronectin expression though multiple signaling pathways under diabetic conditions both in vivo and in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…RSV has been widely explored because of the discovery of antioxidant effects [30]. RSV protects mitochondrial function and mass against stress-induced oxidative damage [31].…”
Section: Discussionmentioning
confidence: 99%